Oral Hygiene Status among Denture and Non-denture Wearers in a Tertiary Health Care Centre: An Analytical Cross-Sectional Study - Mahanta, Swagat Kumar; Prajapati, Dilip; Gurung, Kripa; Shrestha, Rajmee; KC, Smriti; Rijal, Arjun Hari; Adhikari, Bhoj Raj; Lamichhane, Simant (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Introduction: Establishing good oral hygiene has been essential in achieving and maintaining overall physical and emotional well-being throughout life. With the use of dentures, it is believed to worsen the health of the oral cavity if not properly maintained.Objective: To compare the oral hygiene status among denture wearers and non-denture wearers.Methods: An analytical cross-sectional study was conducted from September to October 2023 in the outpatient department of the Dental Department in Dhulikhel. Convenience sampling method was used. A sample of 120 patients was divided into two groups: denture wearers and non-denture wearers. Data were collected and entered into the Microsoft excel and further analysis was done in the SPSS v20. Oral hygiene status, halitosis, and tongue coating were evaluated and compared between the groups.Results: The Simplified Oral Hygiene Index (OHI-S) scores were comparatively higher among denture wearers (3.09±0.92) as compared to non-denture wearers (2.47±0.82). The majority of the denture wearers 26 (43.3%) had poor oral hygiene status. Tongue Coating Index (TCI) scores were almost similar among both groups. The organoleptic score was higher among denture-wearer participants (1.35±0.51) as compared to the non-denture wearers (1.15±0.44).Conclusions: Wearing a denture has an impact on the oral hygiene status and halitosis of an individual. Post-denture delivery instructions and regular follow-ups are recommended to maintain proper oral health.